Sustainable ex-situ remediation of contaminated sediment: A review. (15th October 2021) - Zhang, Yuying; Labianca, Claudia; Chen, Liang; De Gisi, Sabino; Notarnicola, Michele; Guo, Binglin; Sun, Jian; Ding, Shiming; Wang, Lei
Abstract: Routine waterway dredging activities generate huge volumes of dredged sediment. The remediation of dredged contaminated sediment is a worldwide challenge. Novel and sustainable ex-situ remediation technologies for contaminated sediment have been developed and adopted in recent years. In this review paper, the state-of-art ex-situ treatment technologies and resource utilisation methods for contaminated sediment were critically reviewed. By applying different techniques, sediment could been successfully transformed into sustainable construction materials, such as ceramsite, supplementary cementitious materials, fill materials, paving blocks, partition blocks, ready-mixed concrete, and foamed concrete. We highlighted that proper remediation technologies should be cleverly selected and designed according to the physical and chemical characteristics of sediment, without neglecting important aspects, such as cost, safety, environmental impacts, readiness level of the technology and social acceptability. The combination of different assessment methods (e.g., environmental impact assessment, cost-benefit analysis, multi-criteria decision analysis and life cycle assessment) should be employed to comprehensively evaluate the feasibility of different sustainable remediation technologies. We call on the scientific community in a multidisciplinary fashion to evaluate the sustainability of various remediation technologies for contaminated sediment. Graphical abstract: Image 1 Highlights: Review the state-of-the-art treatment and recycling technologies for contaminated sediment. Elaborate immobilisation and removal mechanisms of contaminants in the treated sediment. Introduce evaluation methods for different ex-situ sediment remediation technologies. Provide current limitations and future perspectives for sustainable sediment remediation. Abstract : This paper critically reviewed the state-of-art ex-situ remediation of contaminated sediment and highlighted the valorisation of sediment into construction materials.